2003
DOI: 10.1080/1355260031000137959
|View full text |Cite
|
Sign up to set email alerts
|

The violent reconvictions of sexual offenders

Abstract: The violent reconvictions of a sample of sexual offenders discharged from prison between 1992 and 1996 (who had not been reconvicted of a sexual offence) were examined. The hypothesis was that a proportion of these violent reconvictions would have a sexual motivation. The sample consisted of 104 adult male sexual offenders for whom detailed information regarding their violent reconviction was available. The sample was categorized according to the motivation of the violent reconviction. It was found that a prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Official sources are known to underreport recidivism (Marshall and Barbaree, 1988;Falshaw et al, 2003). Sexual offences have been known to be 'bargained down' (Bagley and Pritchard, 2000;Corbett et al, 2003). The OI provides no record of interventions in prison or later; for example, whether the sex offenders were routinely offered places on a sex offenders' treatment programme, which could affect the rate of recidivism (Hanson et al, 2002;Craig et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…Official sources are known to underreport recidivism (Marshall and Barbaree, 1988;Falshaw et al, 2003). Sexual offences have been known to be 'bargained down' (Bagley and Pritchard, 2000;Corbett et al, 2003). The OI provides no record of interventions in prison or later; for example, whether the sex offenders were routinely offered places on a sex offenders' treatment programme, which could affect the rate of recidivism (Hanson et al, 2002;Craig et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…Serious sexual offences are often ''bargained down'' to violent offences in order to Psychosexual characteristics of sexual offenders 239 secure convictions (Lees, 1996). Corbett, Patel, Erickson, and Friendship (2003) examined the violent reconvictions in 104 sexual offenders (54% rapists, 11% child molesters and 35% other sexual) and found that 12% of violent reconvictions were sexually motivated but that the sexual element of the offence was not recorded. It is possible that violent convictions may mask the true motivation of the offence (Craig, Browne, Beech, & Stringer, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Serious sexual offenses are often bargained down to violent offenses to secure convictions (Bagley & Pritchard, 2000). Corbett, Patel, Erikson, and Friendship (2003) found that 12% of violent reconvictions were sexually motivated but that the sexual element of the offense was not recorded. When considering sexual offenders, some violent convictions may mask the true motivation of the offense.…”
Section: Methodological Limitationsmentioning
confidence: 99%